Indirect Estimations of Lentil Leaf and Plant N by SPAD Chlorophyll Meter - Hossein Zakeri; Jeff Schoenau; Albert Vandenberg; Mohammadreza Tayfeh Aligodarz; Rosalind A. Bueckert (International Journal of Agronomy)
A Soil Plant Analysis Development (SPAD) chlorophyll meter can be used to screen for leaf nitrogen (N) concentration in breeding programs. Lentil (Lens culinaris L.) cultivars were grown under varied N regimes, SPAD chlorophyll meter readings (SCMR) were recorded from the cultivars leaves, and leaf N concentration was measured by combustion. Linear regression and the nonlinear Radial Basis Functions (RBF) neural networks models were employed to estimate leaf N concentration (LNC) based on the SCMR values. The closest estimates of LNC were obtained from the multivariate models in which the combination of plant age, leaf thickness, and SCMR was employed as the independent variable. In comparison, SCMR as the single independent variable in both models estimated less than 50% of LNC variations. The results showed significant effects of soil moisture and plant age on the association of LNC –SCMR as well as the relationship of LNC with plant N, grain yield, and days to maturity. However, the effect of cultivar on the measured variables was negligible. Although lentil N can be diagnosed by comparing SCMR values of the crop with those from a well-fertilized (N fixing) plot, the results did not support using SPAD chlorophyll meter for screening lentil LNC.